PsycEXTRA Dataset 2009
DOI: 10.1037/e640702009-001
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism negatively affects multitasking performance through state anxiety

Abstract: A -Approved for public release; distribution is unlimited.Multitasking is on the rise, both at work and at home. As such, researchers have begun to focus attention on understanding and predicting multitasking performance. Though past research has demonstrated that cognitive predictors correlate positively with multitasking performance, there is reason to believe that non-cognitive factors are likely to predict such performance as well. This study tested for relationships between extraversion, neuroticism, Type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 30 publications
1
12
0
3
Order By: Relevance
“…Variables that have previously been found to predict multitasking behavior in college students include technology innovativeness and use of social networking sites (Zhong, Hardin, and Sun 2011), neuroticism (Poposki, Oswald, and Chen 2009;Wang and Tchernev 2012), and attentional impulsiveness and sensation seeking (Sanbonmatsu et al 2013). One study that had a nonstudent (14-16 years old) sample also found sensation seeking was a predictor of media multitasking, as was gender (Jeong and Fishbein 2007).…”
Section: Media Multitasking and Individual Differencesmentioning
confidence: 98%
“…Variables that have previously been found to predict multitasking behavior in college students include technology innovativeness and use of social networking sites (Zhong, Hardin, and Sun 2011), neuroticism (Poposki, Oswald, and Chen 2009;Wang and Tchernev 2012), and attentional impulsiveness and sensation seeking (Sanbonmatsu et al 2013). One study that had a nonstudent (14-16 years old) sample also found sensation seeking was a predictor of media multitasking, as was gender (Jeong and Fishbein 2007).…”
Section: Media Multitasking and Individual Differencesmentioning
confidence: 98%
“…Not only is neuroticism a predictor of job performance across a variety of occupations (Barrick et al, 2001), neuroticism has also been found to be negatively related to multitasking performance Poposki et al, 2009b;Szymura & Necka, 1998). Highly neurotic individuals are more likely to experience more stress and anxiety that hinders performance in an environment requiring performance on multiple tasks simultaneously, the need for frequent switching of attention, and the presence of time pressures .…”
Section: Non-cognitive Individual Differences and Multitaskingmentioning
confidence: 99%
“…Highly neurotic individuals are more likely to experience more stress and anxiety that hinders performance in an environment requiring performance on multiple tasks simultaneously, the need for frequent switching of attention, and the presence of time pressures . Later research identified differences in anxiety levels elicited by multitasking simulations as a possible reason for this difference, as anxiety partially mediates the relationship between neuroticism and multitasking ability (Poposki et al, 2009b). More specifically, Oswald and colleagues tested multitasking performance in both "routine" and simulated "emergency" settings.…”
Section: Non-cognitive Individual Differences and Multitaskingmentioning
confidence: 99%
See 2 more Smart Citations